Design of Canals - Swamee, P.K; Chahar, B.R (Springer Transactions in Civil and Environmental Engineering, 2015)
The book presents firsthand material from the authors on design of hydraulic canals. The book discusses elements of design based on principles of hydraulic flow through canals. It covers optimization of design based on usage requirements and economic constraints. The book includes explicit design equations and design procedures along with design examples for varied cases. With its comprehensive coverage of the principles of hydraulic canal design, this book will prove useful to students, researchers, and practicing engineers. End-of-chapter pedagogical elements make it ideal for use in graduate courses on hydraulic structures offered by most civil engineering departments across the world.